2012
DOI: 10.1029/2012gl050999
|View full text |Cite
|
Sign up to set email alerts
|

Spacecraft charging near Enceladus

Abstract: [1] In the vicinity of Enceladus, a geologically active moon of Saturn, the modeled spacecraft potential is significantly more negative than indicated by the Cassini Langmuir probe measurements. To understand this potential difference, we introduce two new dust-related charging currents: a) the dust ram current; and b) the dust impact-plasma current, in addition to the customary collection of electrons and ions, and photoemission. Our results show that these dust currents are important at high relative speeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The knowledge of the electron and ion densities helps to constrain the dust size distributions measured by different instruments during the Enceladus flybys and E ring crossings [ Yaroshenko et al ., ; Shafiq et al ., ; Morooka et al ., ; Hill et al ., ]. An accurate electron density also helps to understand the dusty plasma dynamics in the vicinity of Enceladus, which serves as a natural laboratory for studying the dust‐plasma interaction [ Morooka et al ., ; Hsu et al ., , ].…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the electron and ion densities helps to constrain the dust size distributions measured by different instruments during the Enceladus flybys and E ring crossings [ Yaroshenko et al ., ; Shafiq et al ., ; Morooka et al ., ; Hill et al ., ]. An accurate electron density also helps to understand the dusty plasma dynamics in the vicinity of Enceladus, which serves as a natural laboratory for studying the dust‐plasma interaction [ Morooka et al ., ; Hsu et al ., , ].…”
Section: Discussionmentioning
confidence: 99%
“…At higher latitudes and farther away from Saturn, mostly positive pulses were observed. This is consistent with the theory and observation that Cassini spacecraft is negatively charged in the cold dense plasma torus and positively charged in the hot tenuous plasma of the outer magnetosphere [ Wahlund et al ., , ; Morooka et al ., , ; Gustafsson and Wahlund , ; Hsu et al ., , ]. Figure (right) can be compared with Figure c of Wahlund et al .…”
Section: Onboard Dust Detectionmentioning
confidence: 98%
“…The Langmuir probe (RPC‐LAP) on Rosetta indicated that the spacecraft (s/c) had an electrical potential relative to the ambient plasma of about V s/c ≈ −5 V to −20 V [ Edberg et al ., ; Odelstad et al ., ]. It is well‐known that spacecraft, dust grains, etc., can acquire electrical charge (and thus potential) in space due to several types of charging currents [ Hsu et al ., ], including ambient plasma electron and ion currents and photocurrents from absorption of solar photons. The cometary nucleus itself at 3 AU should have an electrical potential.…”
Section: The Rosetta Ion and Electron Spectrometer (Ies) And Datamentioning
confidence: 99%